The Environmental Kuznets Curve Revisited: A Spatial Panel Model with Heterogeneous CoefficientsQ - Schneiter, Pierre; Mellon, Shaibu (Energy economics, 2025)
This paper revisits the Environmental Kuznets Curve (EKC) hypothesis through the lens of spatial econometrics to analyse the relationship between income and emissions of CO, CO2, and CH4 in Swedish municipalities from 2015 to 2021. The study leverages recent developments in spatial econometric methods to relax the homogeneity assumption found in earlier EKC models. The analysis identifies an inverted U-shaped relationship between income and emissions across numerous municipalities: 182 for CO, 128 for CO2, and 158 for CH4 out of 285. The study highlights the importance of spatial econometric models in capturing nuanced income- emissions relationships and spatial spillover effects, often neglected in non-spatial models. Policy implications indicate that economic growth alone may not be enough to lower emissions in all municipalities, highlighting the need for targeted strategies that account for local economic and environmental conditions.